REVIEW PAPERSHypertrophic scars and keloids Part II. Prevention and treatment - Zieliński, Tomasz; Witmanowski, Henryk; Lewandowicz, Edward; Łuczkowska, Magdalena; Kruk-Jeromin, Julia (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Hypertrophic scars and keloids are the result of aberration of the normal wound healing process leading to its overproduction. Clinically, these scars can be disfiguring functionally, aesthetically, or both. Effective treatment of hypertrophic scars and keloids still presents a significant challenge. Various modalities of therapy may be applied, but none of them has been proved entirely successful. Choosing a treatment modality depends on a careful clinical evaluation of the scar with regard to its location, size and time since its formation. In the publication we review data on surgical, pharmacological and physical methods of treatment of hypertrophic scars and keloids. Each of these methods can be applied as monotherapy, but combining them gives better results.